Unveiling Bandgap Evolution and Carrier Redistribution in Multilayer WSe2: Enhanced Photon Emission via Heat Engineering. Issue 2 (5th December 2019) - Li, Yuanzheng; Liu, Weizhen; Xu, Haiyang; Chen, Heyu; Ren, Hang; Shi, Jia; Du, Wenna; Zhang, Wei; Feng, Qiushi; Yan, Jiaxu; Zhang, Cen; Liu, Yichun; et al.
Abstract: Manipulating the bandgap structure and carrier distribution of multilayer transition metal dichalcogenides (TMDs) is crucial for improving their fluorescence efficiency and extending their optoelectronic applications. Herein, the evolution of the conduction band minimum of multilayer WSe2 as a function of the temperature and thickness is experimentally demonstrated and an ≈70‐fold fluorescence enhancement of the K–K direct emission is observed at 560 K in multilayer WSe2 flakes (≈170 nm) by heat engineering. This abnormal enhancement is attributed to thermally driven carrier redistribution achieved via intervalley transfer, which is confirmed by the theoretical calculations and temperature‐dependent time‐resolved photoluminescence. In addition, a threshold temperature of the intervalley transfer is proposed to describe the on‐state of the carrier redistribution model. The corresponding threshold temperature is determined to be ≈580 K, which is consistent with the temperature at which the maximum photoluminescence enhancement is observed. The study provides a useful strategy to optimize the optical and electric performances of multilayer WSe2 and other TMDs materials. Abstract : Manipulating the bandgap structure and carrier distribution can serve as a promising method to improve fluorescence efficiency of multilayer transition metal dichalcogenides. Based on heat engineering, the evolution of conduction band minimum of multilayer WSe2 as a function of temperature and itself thickness and a ≈70‐fold fluorescence enhancement of K–K direct emission at 560 K are obtained, respectively.